Character Education in Islamic Religious Learning: Roles of Teachers, Parents, and Schools at State Junior High School 1 Grobogan - Talitha Khairina; Hafidz Hafidz (FKIP - Universitas Riau, 2026)
Islamic education aims to develop students who are not only intellectually competent but also possess noble character (akhlakul karimah). However, character education in schools is often emphasized on cognitive aspects, while moral and behavioral development receives less attention. This study explores the role of Islamic Religious Education in fostering students’ akhlakul karimah and identifies the challenges and supporting and inhibiting factors in its implementation at State Junior High School 1 Grobogan. This research employed a qualitative approach using in-depth interviews, participatory observation, and document analysis. Participants included Islamic Religious Education teachers, school administrators, students, and parents. Data were analyzed through data reduction, data display, and conclusion drawing to ensure the validity of the findings. The results indicate that students’ akhlakul karimah is influenced by the roles of teachers, parents, and the school environment. Teachers play a central role through modeling, habituation, and discipline, while parental involvement and school climate support character development. The main challenges include negative peer influence, exposure to digital media, limited resources, and inconsistent role modeling from adults. These findings imply that effective character education requires strong collaboration among teachers, parents, and schools to create a supportive moral learning environment.